The Efficacy of Tamsulosin In The Treatment of Ureter Lower Stones: A Prospective Randomized Study - Ceylan, Cavit (Fırat University, 2007)
Objectives: We aimed to determine the efficacy of tamsulosin (0.4 mg/day) as oral expulsive medical therapy in patients who were followed for distal üreter calculi at urology clinic in Elazig Public Hospital. Material and Methods: The study was continued with 102 consecutive patients; 21 female and 30 male was included in Group A (51) with a mean age of 37.2±12.6 (16-62y) and 19 female and 32 male was included in Group B (51) with a mean age of 35.5±11.7 (17-63y). Group A consisted control patients treated with conservative therapy (analgesic, antiemetic), Group B included study patients treated with oral expulsive medical therapy (tamsulosin 0.4 mg/gün) and they were followed 28 days. 30 mg /day deflazacort, lansaprozole 30 mg/day and 2x500 mg /day cinolone with minimal side effects were performed to the groups maximum 10 days. To drink minimum 2 liters of water per a day was offered to all of the patients, 75 mg diclofenac sodium (1.2mg/kg) was performed intramusculary as analgesic when required. Patients who were Stone-free was excluded from the study in Group A and B. The pass of the stones and drug’s side effects were questionaired to the patients at weekly controls. Results: Results and Conclusion: In Group A, 19 patients (37.2%) expulsed stone meanly at 18.1±7.3 days, in Grup B, 40 patients (78.4%) expulsed stone meanly at 5.8±2.7 days. Conclusion: In conclusion, oral expulsive medical therapy can be an approach that must be thought in urether lower stones after the evaluation of the patient exactly. ©2007, Firat University, Medical Faculty

Giriş: Elazığ Devlet Hastanesi üroloji polikliniğinde üreter alt uç taşı nedeniyle izlenen hastalarda oral atılım medikal tedavisi olarak tamsulosinin (0.4 mg/gün) etkinliğini prospektif randomize çalışmayla belirlemeyi hedefledik. Gereç ve Yöntem: Ocak 2003- Aralık 2005 tarihleri arasında, grup A (51) 21 kadın, 30 erkek ve ortalama yaşı 37.2±12.6 (16-62y), grup B (51) ise 19 kadın, 32 erkek ve ortalama yaşı 35.5±11.7 (17-63y) olan toplam 102 hasta ile çalışma sürdürüldü. Grup A, kontrol grubu hastaları olup konservatif tedaviyle (analjezik, antiemetik), grup B çalışma grubu olup, oral atılım medikal tedavisiyle ( tamsulosin 0.4 mg/gün ) 28 gün izlendi. Gruplara maksimum 10 gün minimal yan etkiye sahip 30 mg/gün deflazakort, lansoprazol 30 mg/gün ve 7gün 2x500 mg/gün kinolon oral yoldan verildi. Tüm hastaların günde en az 2 litre su alması önerildi, gerektiğinde ağrı kesici olarak 75 mg diklofenak sodyum (1.2mg/kg) intramuskuler yoldan uygulandı. Grup A ve grup B’de taşı düşüren hastalar takipten çıkarıldı. Haftalık kontrollerde hastaların taş düşürmesi ve ilaç yan etkisi sorgulandı. Grup A’da hastalar 113.2mg/hasta (4.04mg/hasta/gün), grup B’de 33.8mg/hasta (1.2mg/hasta/gün) analjezik kullandılar. Gruplar arası taş atılım oranı, taş atılma süresi, kullanılan analjezik miktarı yönünden önemli fark p:0.000 (p
Üreter Alt Uç Taşlarının Tedavisinde Tamsulosinin Etkinliği: Prospektif Randomize Bir Çalışma